2022
DOI: 10.3389/fbioe.2022.1020300
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharide protects sepsis model rats after cecum ligation and puncture

Abstract: To investigate the protective effect and mechanism of Astragalus polysaccharide (APS) on septic rats, the present project applied APS at concentrations of 400, 600, and 800 mg/kg/d to rats for prophylactic administration for 7 d, and a rat sepsis model was constructed by the cecum ligation and puncture (CLP) method. Forty-eight rats were divided into six groups of eight each. Each experiment was repeated at least three times. Rat serum levels of VD3, 25(OH)D3, 1,25(OH)2D3, IL-6, TNF-α, CRP, sICAM-1, corticoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Additionally, Astragalus polysaccharide has shown immense potential in the treatment of various diseases, including cancer, diabetes, cardiovascular diseases, and liver diseases ( Li et al, 2022b ). Its efficacy extends not only to alleviating these conditions but also to combating sepsis, as revealed by a recent study ( Li et al, 2022c ). This study suggested that the upregulation of adrenocortical VDR activity and vitamin D levels might be the mechanism by which astragalus polysaccharide improves sepsis outcomes.…”
Section: Natural Bioactive Compounds Targeting Vdr Activitymentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, Astragalus polysaccharide has shown immense potential in the treatment of various diseases, including cancer, diabetes, cardiovascular diseases, and liver diseases ( Li et al, 2022b ). Its efficacy extends not only to alleviating these conditions but also to combating sepsis, as revealed by a recent study ( Li et al, 2022c ). This study suggested that the upregulation of adrenocortical VDR activity and vitamin D levels might be the mechanism by which astragalus polysaccharide improves sepsis outcomes.…”
Section: Natural Bioactive Compounds Targeting Vdr Activitymentioning
confidence: 93%
“…The latter is especially significant as these proteins play a crucial role in modulating the gut microbiota flora, specifically, those species that produce short-chain fatty acids. These fatty acids can directly or indirectly mitigate sepsis processes and renal damage induced by sepsis ( Li et al, 2022c ). This is consistent with a previous study that also show the protective effects of astragalus polysaccharide on sepsis-indued acute kidney injury ( Sun et al, 2021 ).…”
Section: Natural Bioactive Compounds Targeting Vdr Activitymentioning
confidence: 99%